دور المسؤولية البيئية في تعزيز ميزتها التنافسية دراسة حالة المؤسسة الوطنية للدهن _سوق اهراس_ - الهام حمايدية; منى بن سلطان (My University, 2021)
Since the industrial revolution, environmental issues began to arise with force, due to industrial progress, and over time, discussions about the environmental responsibility of institutions began to increase, as it became one of the biggest challenges that This study aims to reveal the relationship between the independent variable represented in environmental responsibility and the dependent variable represented in competitive advantage, and this study relied on the descriptive approach in the theoretical aspect, and the analytical approach in the practical aspect, where the A questionnaire was used to know the point of view of the study sample composed of 30 employees and officials of the National Oil Corporation - Ahras Market Unit, and the results were analyzed on the statistical package for the social sciences SPSS. The study found a weak direct relationship between environmental responsibility and competitive advantage. In the end, the study recommended the need to integrate environmental responsibility into its economic strategies and to seek to increase its profits by respecting environmentally friendly products. ............................................................ منذ الثورة الصناعية بدأت المشكلات البيئية تطرح نفسها بشدة، نتيجة التقدم الصناعي ومع مرور الوقت بدأ الحديث عن المسؤولة البيئية للمؤسسات بالتزايد، حيث اصبحت احد اكبر التحديات التي تواجهها ،تهدف هذه الدراسة إلى الكشف عن العلاقة بين المتغير المستقل المتمثل في المسؤولية البيئية والمتغير التابع المتمثل في الميزة التنافسية، ولقد اعتمدت هذه الدراسة على المنهج الوصفي في الجانب النظري، والمنهج التحليلي في الجانب التطبيقي، حيث تم استخدام الاستبيان لمعرفة وجهة نظر عينة الدراسة المكونة من 03 موظف ومسؤول في المؤسسة الوطنية للدهن - وحدة سوق اهراس، وتم تحليل النتائج على برنامج الحزمة . SPSS الإحصائية للعلوم الاجتماعية توصلت الدراسة الى وجود علاقة طردية ضعيفة بين المسؤولية البيئية والميزة التنافسية. في الاخير اوصت الدراسة بضرورة ادماج المؤسسة للمسؤولية البيئية في استراتيجياتها الاقتصادية والسعي الى زيادة فوائدها باحترام المنتجات الصديقة للبيئة.